Etika Dalam Ilmu Pengetahuan - Natriani Syam; Syamsu A Kamaruddin; Abdullah Sinring (Universitas Muhammadiyah Gresik, 2025)
The development and use of science should have a positive impact, but occasionally it has a negative impact on society. Ethics is an important aspect in the world of science that plays a key role in guiding human behavior and serves as the foundation for the responsible development and use of knowledge. Therefore, ethical aspects must serve as a guideline for knowledge developers, namely scientists, as well as knowledge users, so that knowledge can bring benefits to humanity.